Poggers in the chat : an analysis of in-group communication on Twitch - Tay, Debbie Si Ting (Nanyang Technological University, 2020)
Twitch.tv is a streaming platform that has grown and is still growing rapidly since its inception back in 2011. In addition to being a popular video streaming site, users of Twitch have formed their own in-group communication model exclusive to those who are regulars of the site. An integral aspect of this model is Twitch emotes, expressions of various reactions that have been so effective and popular that usage of this niche lexicon has gone past chatspeak and found its way into verbal speech. This paper aims to observe and analyze the methods of communication used between a streamer and their audience, and how each party affects the other’s choice of language. In order to do so, the interaction and communication methods of three Twitch streamers with differing levels of popularity were observed. About 48 hours’ worth streams were collected from each streamer’s channel for observation, and the corresponding chat logs from the streams were also analysed. A survey involving 10 respondents was also carried out to better understand consumer habits and thoughts regarding interaction with the streamer, participation in chat and emote usage. The study found that streamers are recognized by their audience as the center of the conversation, and use emotes to streamline communication between themselves and their audience, especially in the case of high chat activity. The study also found that streamers and audiences affect each other’s choice of emotes and language, because a streamer’s personality directly influences their community’s behaviour, translating into preferences that determine which emotes are favoured or otherwise. Survey participants were also observed to be sensitive to context differences that affected their choice of emote and were more mindful of whether or not to make references to emotes outside of Twitch.